The Making of a Conservationist: J.R. Dymond and His Environments, 1887-1932 - Warecki, George (Ontario History, 2016)
Published accounts of the work of J.R. Dymond, a zoology professor at the University of Toronto, director of the Royal Ontario Museum, and a significant force for conservation in Ontario emphasize his contributions to the natural history movement, and his influence on scientific research and the protection of natural areas in provincial parks. Relatively little attention has been paid to his early life and the local environments that shaped his views of nature. This article uses the concept of “place” to explain how Dymond became a conservationist. His experiences in specific locations—a product of social relations and the landscapes themselves—gave those places meaning and shaped his values. Such environments included the family farm and surrounding countryside in southwestern Ontario’s Metcalfe Township, Strathroy Collegiate Institute, the University of Toronto and nearby natural areas, places in Ottawa, and various lakes in B.C. and Ontario.